Characterization of PD-L1 expression and immune cell infiltration in nasopharyngeal cancer. (April 2017) - Chan, Oscar Siu Hong; Kowanetz, Marcin; Ng, Wai Tong; Koeppen, Hartmut; Chan, Lai Kwan; Yeung, Rebecca Mei Wan; Wu, Haiyan; Amler, Lukas; Mancao, Christoph
Highlights: Programmed death-ligand 1 (PD-L1) is commonly expressed in nasopharyngeal cancer. PD-L1 expression assessed by IHC was not prognostic for clinical benefit in NPC. PD-L1 expression/CD8 infiltration were reduced in most post SoC treatment biopsies. These results provide valuable data for future studies of checkpoint inhibitors. Abstract: Objectives: Locally recurrent or metastatic nasopharyngeal cancer (NPC) remains an important challenge, with more effective and durable therapeutic options needed. Cancer immunotherapy, and in particular therapies that target the PD-L1/PD-1 immune checkpoint pathway, may provide new options to treat NPC patients. This study evaluated PD-L1 and CD8 expression levels and the respective associations with clinical and histopathological characteristics of patients with NPC. Materials and methods: Diagnostic tumour biopsies were obtained before radical radiotherapy with or without chemotherapy from 161 patients with NPC. These biopsies were analysed for PD-L1 expression levels on tumour cells (TC) and tumour-infiltrating immune cells (IC), and for CD8 T-cell infiltration. Results were correlated with baseline characteristics and clinical outcomes with standard-of-care treatment regimens. Additionally, pre- and post-treatment–paired tumour samples were analysed (n = 146). Results: 75% of tumours expressed PD-L1 on IC and 24% on TC. Baseline clinical characteristics of stage, sex and age did not correlate with PD-L1 expression. Additionally, overall survival and progression-free survival of standard-of-care treatment did not correlate with baseline PD-L1 expression. CD8 levels did correlate with clinical outcomes; however, results were confounded by other baseline characteristics. After treatment, PD-L1 expression dropped a median of 1.5% on IC and a median of 2.75% on TC. Median CD8 expression dropped 1.9%. Conclusions: Majority of NPC biopsy samples demonstrated PD-L1 expression on ⩾1% of IC, with fewer expressing PD-L1 on TC. In contrast to previous smaller studies, no prognostic value was observed for PD-L1 expression levels in patients with NPC.